Bone age assessment practices in infants and older children among Society for Pediatric Radiology members. - Breen, Micheál; Tsai, Andy; Stamm, Aymeric; Kleinman, Paul; Breen, Micheál A; Kleinman, Paul K (Pediatric Radiology, 2016)
Background: Numerous bone age estimation techniques exist, but little is known about what methods radiologists use in clinical practice.Objective: To determine which methods pediatric radiologists use to assess bone age in children, and their confidence in these methods.Materials and Methods: Society for Pediatric Radiology (SPR) members were invited to complete an online survey regarding bone age assessment. Respondents were asked to identify the methods used and their confidence with their technique for the following groups: Infants (<1 year old), 1- to 3-year-olds and 3- to 18-year-olds.Results: Of the 937 SPR members invited, 441 responded (47%). For infants, 70% of respondents use the hand/wrist method of Greulich and Pyle, 27% use a hemiskeleton method (e.g., Sontag or Elgenmark), and 14.4% use the knee method of Pyle and Hoerr. Of these respondents, 34% were not confident with their technique. For 1- to 3-year-olds, 86% used Greulich and Pyle, and 19% used a hemiskeleton method; 21% were not confident with their technique in this age group. For 3- to 18-year-olds, 97% used Greulich and Pyle, and only 6% of respondents were not confident with their technique in this category. A logistic regression analysis demonstrated that the chronological age of the patient had the greatest impact on reader confidence, with the odds ratios for confidence being 4 times greater in the 3- to 18-year-olds category compared to the younger groups.Conclusion: For children older than 3 years, the majority of pediatric radiologists are very confident in their use of Greulich and Pyle for bone age assessment. However a variety of methodologies are used when assessing bone age in infants and younger children, and pediatric radiologists are less confident assessing bone age in these children. This survey highlights the need for a consensus protocol on bone age assessment of younger children and infants that provides readers with a higher degree of confidence.